Investigating the Compatibility of IRI and ASAPS Models in Predicting the foF2 Ionospheric Parameter over the Mid Latitude Region - Ja’far, Ja’far M.; Hadi, Khalid A. (Iraqi Journal of Science, 2021)
In this research, an investigation for the compatibility of the IRI-2016 and ASAPS international models was conducted to evaluate their accuracy in predicting the ionospheric critical frequency parameter (foF2) for the years 2009 and 2014 that represent the minimum and maximum years of solar cycle 24. The calculations of the monthly average foF2 values were performed for three different selected stations distributed over the mid-latitude region. These stations are Athens - Greece (23.7o E, 37.9 o N), El Arenosillo - Spain (-6.78 o E, 37.09 o N), and Je Ju - South Korea (124.53 o E, 33.6 o N). The calculated values using the two tested models were compared with the observed foF2 datasets for each of the three selected locations. The results showed that the two tested models gave good and close results for all selected stations compared to the observed data for the studied period of time. At the minimum solar cycle 24, the ASAPS model showed in general better values than the IRI-2016 model at Athens, El Arenosillo and Je Ju stations for all tested methods. At maximum solar cycle 24, the IRI-2016 model showed higher and closer values to the observed data at Athens and El Arenosillo stations, while the ASAPS model showed better values at Je Ju station.